Prototyping with Origami Studio : a beginner's guide (O'Reilly, 2018)
"Today's world is all about smart phone and computers, but creating the apps and websites that run on these devices can take a year or more to complete. Prototypes are typically non-functioning models of apps and websites that give developers and designers the edge on this lengthy creation process. Why? Because prototypes can be assembled in as little as a single day, saving them time and money. This course teaches you how to use Origami, a prototyping tool created by designers at Facebook that makes it easy to create prototypes for smart apps and websites. You'll explore Origami's interface, learn the principles of prototyping, and gain experience assembling and disseminating a basic prototype."--Resource description page